Pengembangan Perangkat Pembelajaran Berbasis Proyek untuk Keterampilan Komunikasi Ilmiah Mahasiswa - Fitria Eka Wulandari; Jamilatur Rohmah; Yuli Astutik (International Consortium of Education and Culture Research Studies, 2019)
The purpose of this research is the development of project-based learning tools in teaching students scientific communication skills. The development of these learning devices includes syllabus, learning implementation plans (RPP), student activity sheets (MFIs), evaluation instruments for student communication skills, where these devices are developed using project-based learning models. Learning tools that have been created and that will be used in the learning process have valid and reliable judgments. The stages of developing this learning device are: (1) student scientific communication is carried out in the literature; (2) curriculum, teaching materials, indicators of scientific communication skills, learning characteristics used, characteristics and abilities of students; (3) conduct the preparation of learning evaluations; (4) carry out construct validation; (5) analyze the results of construct and content validation; (6) hold a trial certificate; (7) analysis of trial results. The analysis of the results of the validation of project-based learning tools in training valid and reliable student scientific communication skills.